If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6b + 9 = -4b + 28 Reorder the terms: 9 + 6b = -4b + 28 Reorder the terms: 9 + 6b = 28 + -4b Solving 9 + 6b = 28 + -4b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '4b' to each side of the equation. 9 + 6b + 4b = 28 + -4b + 4b Combine like terms: 6b + 4b = 10b 9 + 10b = 28 + -4b + 4b Combine like terms: -4b + 4b = 0 9 + 10b = 28 + 0 9 + 10b = 28 Add '-9' to each side of the equation. 9 + -9 + 10b = 28 + -9 Combine like terms: 9 + -9 = 0 0 + 10b = 28 + -9 10b = 28 + -9 Combine like terms: 28 + -9 = 19 10b = 19 Divide each side by '10'. b = 1.9 Simplifying b = 1.9
| (-8)/(x+6)=-5 | | 5/(n-12)=-1/n | | 4z^2-16z+12=0 | | x^2(x^2+3x+2)= | | 3y+2.5x-3.7=0 | | x=-22+-6w | | -110=2(1+8) | | 2y^2=-y+10 | | 4-5k-6=-4k-1 | | (6/7)x=24 | | 7x+4=5x-1 | | 2=f/2 | | -182=-6(7-6n)-n | | 4z^2-16+12=0 | | 7x+3/2-9x-8/4=6 | | -22-x=3w-w+4w | | 4/5x+4/3+2x | | 1/5x-y=76 | | -7p-(-7+5p)=-4(3p-7) | | 5(1+7)-5=175 | | x+4/15=-1 | | (7x^2-7x+8)+(9x^3-5x)= | | 3(x+3)+12=6x+3 | | 5(2a-4b)= | | -4(n+6)=12 | | 19=4+3v | | -x-4+3x=x-3+1 | | 7(x+5)=13 | | 4-6a+4a=-115(7-2a) | | 5x+47= | | 11/6x6/35 | | 4(2a-6)+8b= |